The Genre of a Grant Proposal in the Modern Teaching Context: Challenges and Possibilities - T. B. Alenkina (Высшее образование в России, 2023)
Nowadays attaining a grant is a criterion of success for an early-career researcher and an important indicator of effective work of a university as a research-based and corporate institution. During its thirty-year history in Russia, grants have become a traditional and even routine practice for every Russian PhD student and an early-career researcher. Like their international colleagues, Russian researchers often don’t get sufficient support from their scientific advisor and an academic writing expert. A few attempts to improve current situation have been made in a number of research universities. One of such cases is a course “Grant Writing” that has been recently implemented in the English-language writing-intensive program of the Moscow Institute of Physics and Technology. The complex aim or the paper can be explained by the multidimensional nature of a grant. After characterizing a grant proposal as an up-to-date text genre in the international and interdisciplinary context in the framework of Genre Field Analysis, we consider the full process of applying for a grant in real-life environment and classroom settings. Finally, in the lens of Critical Genre Analysis, the qualitative analysis of the introductory sections of Russian grant proposals is conducted. The modern genre theory gives the basis for using a combination of methods in our research. In the lens of Genre Field Analysis, the sociopragmatic approach to the grant proposal provides an opportunity to get acquainted with the modern practices of applying for a grant, while Critical Genre Analysis may contribute to the deeper understanding of the text production mechanisms. The synthesis of theory and practice and its role could be seen in the qualitative analysis of grant proposals written by PhD students, attendees of the course “Grant Writing” at the Moscow Institute of Physics and Technology. The findings give evidence for insufficient disciplinary expertise and substitution of one genre – a grant proposal – by another one, more familiar for Russian students, – a research paper and an abstract. The obtained results testify in favor of the implementation of the course “Grant Writing” as well as other genre-based courses deeply rooted in the cross-disciplinary context and aimed at developing the researcher competence.